H3K27me3 demethylase UTX regulates the differentiation of a subset of bipolar cells in the mouse retina. (14th April 2020) - Umutoni, Daisy; Iwagawa, Toshiro; Baba, Yukihiro; Tsuhako, Asano; Honda, Hiroaki; Aihara, Makoto; Watanabe, Sumiko
Abstract: Di‐ and trimethylation of lysine 27 on histone 3 (H3K27me2/3) is a critical gene repression mechanism. We previously showed that down‐regulation of the H3K27 demethylase, Jumonji domain‐containing protein 3 (JMJD3), resulted in a reduced number of protein kinase C (PKC)α‐positive rod ON‐bipolar cells. In this work, we focused on the role of another H3K27 demethylase, ubiquitously transcribed tetratricopeptide repeat X chromosome (UTX), in retinal development. UTX was expressed in the retinal progenitor cells of the embryonic mouse retina and was observed in the inner nuclear layer during late retinal development and in the mature retina. The short hairpin RNA‐mediated knockdown of Utx in a mouse retinal explant led to a reduced number of PKCα‐positive rod ON‐bipolar cells. However, other retinal subtypes were unaffected by this knockdown. Using a retina‐specific knockout of Utx in mice, the in vivo effects of UTX down‐regulation were examined. Again, the number of PKCα‐positive rod ON‐bipolar cells was reduced, and no other apparent phenotypes, including retinal progenitor proliferation, apoptosis or differentiation, were observed. Finally, we examined retina‐specific Utx and Jmjd3 double‐knockout mice and found that although the number of rod ON‐bipolar cells was reduced, no additional effects from the loss of Utx and Jmjd3 were observed. Taken together, our data show that UTX contributes to retinal differentiation in a lineage‐specific manner. Abstract : Utx is expressed in inner nuclear layer in developing mature retina. Utx plays essential roles for appropriate differentiation of rod bipolar cells in retina.